PENGARUH DESTINATION IMAGE, TRAVEL MOTIVATION, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG (STUDI KASUS PADA WISATAWAN NUSANTARA MUSLIM DI PANTAI CARITA PANDEGLANG BANTEN) - Rina Astini; Indah Sulistiyowati (Universitas Mercu Buana, 2015)
This research aims to know influence of destination image, travel motivation, and service quality on visitor satisfaction. The object for this research is Carita Beach Pandeglang - Banten. The study sample consisted of 150 respondents. The sampling technique in this research is Convinience Sampling, using a type of causal research. Hypothesis testing using Structural Equation Modeling (SEM). The result of this research shows that travel motivation and service quality has the significant influence toward customer satisfaction, while the destination image has not influence toward visitor satisfaction. It is has been proven form the result of hypothesis test that have been result on LISREL 8.70 program also showed a significant influence of the two variables and the negative value of one variable. Therefore, the accepted assumption is, there is two independent variables which supports the hypothesis and one independent variable that not support the hypothesis. Keywords: destination image, travel motivation, servic quality, visitor satisfaction.